Weak investment dampens Europe's growth - Guido Baldi; Ferdinand Fichtner; Claus Michelsen; Malte Rieth (DIW Economic Bulletin, 2014)
In the course of the economic and financial crisis, investment activity, which was not very strong to begin with, in Europe and especially the Eurozone caved in. In relation to gross domestic product, fixed capital formation declined by four percentage points since 2008. Already prior to the crisis, investment activity was rather weak in parts of the Eurozone - amongst others in Germany. This finding is indicated by model simulations which account for country-specific macroeconomic conditions. On the other hand, especially in southern European economies, investment - mostly in the home construction sector - was markedly high before the crisis. These investments were however mainly financed by capital inflows from abroad. In the course of the crisis, foreign direct investment slumped and so did investment activity in these countries which has not been counterbalanced by higher investments in other parts of the monetary union. As a result, current investment in the Eurozone remains markedly below the level corresponding to macroeconomic conditions. When measured against this baseline, there was an underinvestment of around two percent on average in relation to gross domestic product between 2010 and 2012. This is associated with significant reductions in growth in the short and long run since the capital stock needed to maintain production capacity is growing rather slowly. If investment activity in the Eurozone had been correspondingly stronger, potential growth in the monetary union could have been 0.2 percentage points higher than observed since the crisis.
Keywords: E22; E27; F21; 330; investment; potential growth; construction